Taste Perception of Sweet, Sour, Salty, Bitter, and Umami and Changes Due to l-Arginine Supplementation, as a Function of Genetic Ability to Taste 6-n-Propylthiouracil - Melis, Melania; Tomassini Barbarossa, Iole (Nutrients, 2017)
Behavioral reaction to different taste qualities affects nutritional status and health. 6-n-Propylthiouracil (PROP) tasting has been reported to be a marker of variation in taste perception, food preferences, and eating behavior, but results have been inconsistent. We showed that l-Arg can enhance the bitterness intensity of PROP, whilst others have demonstrated a suppression of the bitterness of quinine. Here, we analyze the taste perception of sweet, sour, salty, bitter, and umami and the modifications caused by l-Arg supplementation, as a function of PROP-taster status. Taste perception was assessed by testing the ability to recognize, and the responsiveness to, representative solutions of the five primary taste qualities, also when supplemented with l-Arg, in subjects classified as PROP-tasting. Super-tasters, who showed high papilla density, gave higher ratings to sucrose, citric acid, caffeine, and monosodium l-glutamate than non-tasters. l-Arg supplementation mainly modified sucrose perception, enhanced the umami taste, increased NaCl saltiness and caffeine bitterness only in tasters, and decreased citric acid sourness. Our findings confirm the role of PROP phenotype in the taste perception of sweet, sour, and bitter and show its role in umami. The results suggest that l-Arg could be used as a strategic tool to specifically modify taste responses related to eating behaviors.